2004
DOI: 10.1002/marc.200400050
|View full text |Cite
|
Sign up to set email alerts
|

Free‐Radical Termination Kinetics Studied Using a Novel SP‐PLP‐ESR Technique

Abstract: Summary: A novel method for measuring termination rate coefficients, kt, in free‐radical polymerization is presented. A single laser pulse is used to instantaneously produce photoinitiator‐derived radicals. During subsequent polymerization, radical concentration is monitored by time‐resolved electron spin resonance (ESR) spectroscopy. The size of the free radicals, which exhibits a narrow distribution increases linearly with time t, which allows the chain‐length dependence of kt to be deduced. The method will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
144
1
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(160 citation statements)
references
References 17 publications
12
144
1
3
Order By: Relevance
“…[37] First, the data were plotted as log(c R 0 /c R -1) versus logt, where c R 0 is the value of c R immediately after the laser pulse. The rationale for this approach [38] is the equation…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[37] First, the data were plotted as log(c R 0 /c R -1) versus logt, where c R 0 is the value of c R immediately after the laser pulse. The rationale for this approach [38] is the equation…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…[39] It suggests looking for linear regions in a plot of log(c R 0 /c R -1) versus logt, and taking the slope of these as 1-α, from which it is trivial to determine α. [38] INSERT Figure 2 An example of this procedure is given in Figure 2. Two straight-line regions are evident, suggesting composite-model behavior.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The discussed trends hold for RP in general, the presented equations for steady state only. Using the latter it has been shown that simple steady-state experiments can yield good information on CLDT, although there is no disputing that single-pulse PLP remains the method of choice for such studies [10,11] (see Table 1). In particular the transfer limit is recommended as an important but little realized phenomenon: it can have the guise of 'classical' kinetics (e.g., 〈k t 〉 invariant with R init ) where actually CLDT is occurring.…”
Section: Resultsmentioning
confidence: 99%
“…Although recent theoretical [9] and experimental [10,11] work has shown that this two-parameter model is an oversimplification of reality, it is a nice model to use for calculations, as it clearly exposes the general effects of CLDT on RP kinetics, [12][13][14] and these trends are essentially the same for more complex homo-termination models. [9] The same also holds for cross-termination models, [12][13][14] and so the simplest one will be employed here unless otherwise stated:…”
Section: The Competition Between Termination and Transfermentioning
confidence: 99%